Specificity of Cognitive Bias in Recognition of Emotions in the Face in Old Age - Melehin A.I.; Sergienko E.A. (Клиническая и специальная психология, 2019)
The article shows that in comparison with people aged 55-60 years in the groups of 61-74 and 75-90 years there are symptoms of age-specific socio-cognitive deficits in the recognition of emotions: changes in response time to emotional stimulus in the direction of slowdown; difficulties in fine differentiation of emotions of joy and sadness; the effect of high emotional intensity for a more accurate definition of emotions; cognitive shift in attention and interpretation of socio-emotional information. At a later age, there is a combined cognitive bias in the recognition of emotions in the face. More dominated bya positive shift. Unlike people 75-90 years in groups 55-60 and 61-74 years better recognize emotions of fear and sadness, than 75-90 years. It is more difficult to recognize anger at a later age. The lack of definition of neutral emotional expressions, which is accompanied by the phenomenon of depressive displacement, is described. General and age-specific predictors of recognition and differentiation of emotions in the face at a later age are identified.